Effective Components of a Research-Oriented Curriculum - Aghakasiri, Neda; Nourian, Mohammad; samiee zafarghandi, morteza (International Journal of Education and Cognitive Sciences, 2022)
Purpose: This study aims to identify and synthesize the key components influencing a research-oriented curriculum in education. Methods and Materials: The study follows a synthesis research (meta-synthesis) approach using the inductive content analysis model. The Sandelowski and Barroso (2007) method was employed, consisting of seven stages: formulating the research question, conducting a systematic review of literature, selecting relevant studies, extracting data, analyzing and synthesizing findings, performing quality control, and presenting results. A total of 719 articles were identified through systematic searches in major databases such as ERIC, ScienceDirect, Taylor & Francis, and Springer. After filtering and quality assessment, 25 studies from the period 2010-2024 were selected for final analysis. Findings: The study identified five key categories influencing the research-oriented curriculum: individual acceptance, educator competency, school-related factors, educational system flexibility, and cultural considerations. Each category is subdivided into multiple dimensions, such as technological acceptance, professional competencies of educators, school management, and the culture of quality and evaluation. In total, 75 codes and 20 sub-categories were identified, showing the need for a multi-layered approach, integrating managerial, psychological, and sociological perspectives in curriculum development. Conclusion: The findings underscore the importance of systemic support, teacher competency, and cultural shifts to effectively implement a research-oriented curriculum. The study highlights the need for institutional flexibility, adequate resources, and teacher training in research facilitation. By addressing individual, institutional, and societal dimensions, the proposed curriculum model offers a structured and adaptable framework that promotes research-based learning in educational systems.